(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the nature of the role of educational courses and the stakeholders involved in the practicum (field training) program in the pedagogical preparation of student teachers from the perspective of eighth-semester female students at Abu-Isa Faculty of Education, University of Zawia. The descriptive-analytical approach was utilized. The research population consisted of all eighth-semester female students across all scientific disciplines who actively studied during the Spring 2026 semester, totaling 209 students. A representative sample of 85.17% was selected, comprising 178 female students. A questionnaire was developed, consisting in its final form of 43 items distributed across four main domains: the educational courses domain, the academic supervisor domain, the cooperating subject teacher domain, and the cooperating school principal domain. The content validity and suitability of the instrument for its intended objectives were verified using face validity. Reliability was also established, yielding a reliability coefficient of 0.91 using Cronbach’s alpha. The study revealed several key findings: The overall role of educational courses in the pedagogical preparation of student teachers at the Abu-Isa Faculty of Education received a "very high" approval level, with a general mean of 4.55 and a standard deviation of 0.34. The role of the academic supervisor in pedagogical preparation received a "high" approval level, with a general mean of 4.14 and a standard deviation of 0.42. The role of the cooperating subject teacher in pedagogical preparation also achieved a "high" approval level, with an overall mean of 3.96 and a standard deviation of 0.38. Finally, the overall role of the school principal in the pedagogical preparation of student teachers received a "moderate" approval level, with a general mean of 3.33 and a standard deviation of 0.46.